2013
DOI: 10.1271/bbb.130216
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bioactive Steroids from theStropharia rugosoannulataMushroom and Absolute Configuration of Strophasterol B

Abstract: The absolute configuration of strophasterol B (1) isolated from the fruiting bodies of Stropharia rugosoannulata was determined by an X-ray crystallographic analysis. Three compounds (2 to 4) were isolated from the mushroom which suppressed or promoted lettuce growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 5 publications
0
25
0
2
Order By: Relevance
“…[3] Thep resenilins (6-8 transmembrane proteins) are mainly localized to the endoplasmic reticulum, where they are part of the g-secretase protein complex that cleaves APP to generate Ab peptides.T he resulting amyloidogenic peptides can damage neurons by inducing membrane-associated oxidative stress,t hereby rendering neurons vulnerable to Ca 2+ overload, particularly under conditions of impaired mitochondrial energy production. [6] While the structures of the former two (strophasterols Aand B, 1A and 1B)h ave been unequivocally determined by singlecrystal X-ray diffraction, [7] thes tructures of strophasterols C and D( 1C and 1D)r emain uncertain with regard to their relative and absolute configuration. [5] Strophasterols A-D (1A-D;F igure 1), four secosterols with an unprecedented carbon skeleton, have recently been isolated from the mushroom Stropharia rugosoannulata, which is abundant in the northern temperate zone.…”
mentioning
confidence: 99%
“…[3] Thep resenilins (6-8 transmembrane proteins) are mainly localized to the endoplasmic reticulum, where they are part of the g-secretase protein complex that cleaves APP to generate Ab peptides.T he resulting amyloidogenic peptides can damage neurons by inducing membrane-associated oxidative stress,t hereby rendering neurons vulnerable to Ca 2+ overload, particularly under conditions of impaired mitochondrial energy production. [6] While the structures of the former two (strophasterols Aand B, 1A and 1B)h ave been unequivocally determined by singlecrystal X-ray diffraction, [7] thes tructures of strophasterols C and D( 1C and 1D)r emain uncertain with regard to their relative and absolute configuration. [5] Strophasterols A-D (1A-D;F igure 1), four secosterols with an unprecedented carbon skeleton, have recently been isolated from the mushroom Stropharia rugosoannulata, which is abundant in the northern temperate zone.…”
mentioning
confidence: 99%
“…Great Lakes 366; Takii Co., Ltd., Japan) were used in this study. Bioassay: growth regulating activity against lettuce [1][2][3] .…”
Section: Methodsmentioning
confidence: 99%
“…A novel compound (1) and a known one (2) were isolated from the fruiting bodies of Tricholoma flavovirens. Their structures were determined by the interpretation of spectroscopic data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [61,62] reported the isolation of four new sterols having a very unique and unprecedented carbon skeleton, strophasterols A-D (95-98), from the fruiting bodies of Stropharia rugosoannulata (Fig. 1.15).…”
Section: Sterols Bearing 5a6a-epoxy Groupmentioning
confidence: 99%